Intratumoral microbiome and gastrointestinal cancers - Li, Shengnan; Li, Qian; Lu, Wei (Frontiers in Oncology, 2022)
Emerging studies have revealed the role of microbiota in regulating tumorigenesis, development, and response to antitumor treatment. However, most studies have focused on gut microbiota, and little is known about the intratumoral microbiome. To date, the latest research has indicated that the intratumoral microbiome is a key component of the tumor microenvironment (TME). The TME can promote a heterogeneous immune microenvironment and reprogram tumor metabolism to induce tumor invasion and metastasis. In this review, we summarize existing evidence on the intratumoral microbiome of gastrointestinal cancers and reveal their crosstalk with TME. This will provide a better understanding of this emerging field and help to explore new therapeutic approaches for cancer patients by targeting the intratumoral microbiome.